Performance Study of Ultraviolet AlGaN/GaN Light-Emitting Diodes Based on Superlattice Tunneling Junction - Zhuang Zhao; Yang Liu; Peixian Li; Xiaowei Zhou; Bo Yang; Yingru Xiang; Junchun Bai (Micromachines)
In this study, we aim to enhance the internal quantum efficiency (IQE) of AlGaN-based ultraviolet (UV) light-emitting diodes (LEDs) by using the short-period AlGaN/GaN superlattice as a tunnel junction (TJ) to construct polarized structures. We analyze in detail the effect of this polarized TJ on the carrier injection efficiency and investigate the increase in hole and electron density caused by the formation of 2D hole gas (2DHG) and 2D electron gas (2DEG) in the superlattice structure. In addition, a dielectric layer is introduced to evaluate the effect of stress changes on the tunneling probability and current spread in TJ. At a current of 140 mA, this method demonstrates effective current expansion. Our results not only improve the performance of UV LEDs but also provide an important theoretical and experimental basis for future research on UV LEDs based on superlattice TJ. In addition, our study also highlights the key role of group III nitride materials in achieving efficient UV luminescence, and the polarization characteristics and band structure of these materials are critical for optimizing carrier injection and recombination processes.